Kurnia's Web-Based Drill Method Can Measure the Level of Toothbrushing Skills of Blind Children - Aprianti, Kurnia; Djamil, Masrifan; Ningtyas, Endah Aryati Eko (Jurnal Kesehatan Gigi, 2024)
Background: Blind children have limited vision so that the health of the oral cavity is lower than that of children with normal vision. To improve the dental and oral health of blind children, a change in skills is needed. Choosing the right method of delivering educational material is very helpful in changing target skills. Kurnia's Web-based Drill method with audio modification can be an innovation in providing dental and oral health education. Where audio media that relies on sound can help optimize the sense of hearing that is still functioning so that the message conveyed can be easily remembered and understood by blind children.Research Objective: Build a web-based model of Kurnia's Drill method to improve toothbrushing skills in blind children.Methods: Research and Development (R&D) and model testing (Quasi-Experimental Control Group Pretest and Posttest Design studies). The research subjects of blind children were divided into 2 groups, namely intervention and control. The results of the model design are validated by experts. The data were tested using intraclass, paired t-test and independent t-test correlation coefficients.Results: Kurnia's Drill web-based method is feasible as an educational model for dental health maintenance in blind children (p= 0.000). The implementation of this model effectively improved the brushing skills of blind children (p= 0.047) and decreased the debris index of blind children (p= 0.000) compared to the control group.Conclusion: Kurnia's Drill web-based method effectively improves brushing skills and decreases debris index in visually impaired children.Â